Legal Principles of Procedural Activity and Interaction of Employees of Operative Divisions at Execution of Instructions of Interrogators, Investigators, Prosecutors in Regard to Carrying out Secret Investigative (Search) Actions - O. O. Yukhno (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article provides a retrospective analysis of the provisions of legislative acts of Ukraine, decisions of the Constitutional Court of Ukraine and the European Court of Human Rights, as well as some national criminal procedural legislation and departmental regulations on legal grounds for procedural activities and interaction of operative units to execute written instructions of interrogators, investigators, prosecutors on investigative (search) actions and secret investigative (search) actions. The author has made a retrospective analysis of the introduction of this amendment to the Criminal Procedural Code of Ukraine since 2012, as well as the legal grounds for its use in pre-trial investigation and has focused on the conclusions about its significant prevalence in law enforcement activities of pre-trial investigation, and in connection with recent amendments in the legislation also in the initial practice of the inquiry agencies of the National Police of Ukraine. The author researched positions of scholars and representatives of scientific schools in relation to the conceptual apparatus and the essence of the concept of “interaction” in general, as well as “interaction” between pre-trial investigation and inquiry agencies and operative police units in this direction. Special attention has been paid to the study of the peculiarities of forms of interaction and its subjects in criminal proceedings, as well as the existing legislative and practical issues concerning the compliance with operative deadlines of police orders of interrogators, investigators and prosecutors and has suggested the ways to solve them in practice and, in particular, at the legislative level.